Method for preparing activated carbon from waste tire pyrolytic carbon black
Through the method of multi-stage pyrolysis and multi-process synergistic method, the purity and pore structure of the pyrolysis carbon black of waste tires are optimized, and the problems of insufficient purity and unstable pore structure in the existing technology are solved, which significantly improves the adsorption performance and chemical stability of activated carbon, and is suitable for high-end application fields.
Patent Information
- Application Number
- CN202510039510.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the purity of the pyrolytic carbon black of waste tires is insufficient, the pore structure is difficult to optimize and the process energy consumption is high, making it difficult to meet the needs of high-end applications such as water treatment, gas adsorption and catalysis.
The purity and pore structure of carbon black are optimized, and the specific surface area and adsorption performance of activated carbon is further improved through freeze-drying and solvent heat treatment.
It significantly improves the specific surface area and adsorption performance of activated carbon, solves the problems of insufficient purity and unstable pore structure, and reduces process energy consumption, making it suitable for water treatment, gas adsorption and catalyst support.
Smart Images

Figure CN119873818A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waste tire utilization, and in particular to a method for preparing activated carbon by pyrolyzing carbon black from waste tires. Background Art
[0002] At present, the treatment of waste tires mainly adopts pyrolysis technology to decompose them into pyrolysis gas, pyrolysis oil and pyrolysis carbon black. Pyrolysis carbon black, as a solid carbon material, is widely used in the field of fillers and adsorbents. The existing technology usually obtains pyrolysis carbon black through simple pyrolysis and basic treatment, but its performance is difficult to meet the needs of high-end applications, such as water treatment, gas adsorption and catalysis.
[0003] However, the carbon black in the pyrolysis process has a high impurity content, a large proportion of amorphous carbon, insufficient purity, a single activation method, and a pore structure that is difficult to optimize, resulting in insufficient specific surface area and adsorption performance. The process has high energy consumption and is easy to damage the pore structure of the material, affecting the stability and service life of the activated carbon. Therefore, an efficient and low-energy improvement method is needed to improve the performance and application value of pyrolytic carbon black. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0005] To this end, the purpose of the present invention is to propose a method for making activated carbon using pyrolytic carbon black from waste tires. By introducing a process combining multi-stage pyrolysis, electromagnetic assisted heating, plasma treatment and deep activation, the purity and pore structure of pyrolytic carbon black are optimized. At the same time, through surface functional group regulation and freeze-drying technology, the specific surface area and adsorption performance of activated carbon are greatly improved, solving the problems of insufficient purity, difficult pore structure optimization and high process energy consumption in the prior art.
[0006] To achieve the above object, the present invention proposes a method for preparing activated carbon by pyrolyzing carbon black from waste tires, comprising the following steps:
[0007] S1. Composite separation of waste tire pyrolysis carbon black:
[0008] a. In the first stage, low-temperature pyrolysis is carried out at 250-400℃ to decompose the volatile components in the tire and avoid damage to the carbon black structure;
[0009] b. In the second stage, medium-temperature pyrolysis is carried out at 400-600°C to generate gas phase products and primary carbon black, thereby enhancing the carbonization degree of carbon black;
[0010] c. In the third stage, high temperature pyrolysis is carried out at 600-750°C to strengthen the graphitization structure and chemical stability of carbon black;
[0011] Electromagnetic assisted heating technology is used in the graded pyrolysis process, and trace oxidants are introduced for controlled oxidation to optimize the initial activity of the carbon black surface;
[0012] S2, Selective dynamic screening and magnetic impurity removal, the pyrolysis products are dynamically screened through an airflow classification device to separate high-purity carbon black particles with a particle size of less than 10 microns, and magnetic separation technology is used to remove metal impurities and residual steel wire, and the purity of carbon black reaches more than 95%;
[0013] S3, carbon skeleton structure strengthening treatment, the screened pyrolytic carbon black is placed in a plasma reactor, and low-temperature plasma treatment (100-200°C) is performed in a mixed atmosphere of nitrogen and a small amount of hydrogen to remove amorphous carbon and generate a stable carbon skeleton structure through hydrogenation;
[0014] S4, surface functional group regulation, placing the plasma-treated pyrolytic carbon black in a gas-solid mixed reaction device, introducing a mixed gas of ozone and water vapor, and performing a surface functional group regulation reaction at 80-150°C to generate a large number of hydroxyl, carboxyl and ester functional groups, thereby improving the surface activity of the carbon black;
[0015] S5, deep activation treatment, mixing the surface-modified carbon black with potassium hydroxide solution in a mass ratio of 1:2-3, and performing wet activation reaction in an autoclave at 180-250°C for 2-4 hours; then, heating the activated carbon black to 700-900°C under vacuum conditions for high-temperature activation, while introducing a mixed gas to further optimize the pore structure and increase the specific surface area;
[0016] S6, post-treatment of activated carbon, the activated carbon product is quickly cooled to room temperature, repeatedly washed with deionized water until neutral, and dried by freeze drying (-40°C to -60°C) to retain the integrity of the pore structure, and finally a high-performance activated carbon product is obtained;
[0017] S7. Performance optimization and functional orientation. The prepared activated carbon is subjected to pore regulation and structural orientation treatment. Through solvent thermal treatment (using ethanol or acetic acid solution to react at 120-160°C for 6-8 hours), the proportion of micropores, mesopores and macropores on the surface of the activated carbon is regulated to meet the pore size requirements of different application scenarios.
[0018] The method of preparing activated carbon by pyrolyzing carbon black from waste tires adopts electromagnetic assisted heating combined with a pyrolysis technology of a trace oxidant to optimize the generation of functional groups on the surface of carbon black, and at the same time improves the purity and particle size uniformity of carbon black through airflow classification and magnetic separation technology, enhances the stability and graphitization degree of the carbon skeleton through low-temperature plasma treatment, and regulates the surface functional group density through the synergistic effect of ozone and water vapor, laying a foundation for improving the adsorption performance, optimizes the pore structure through the combination of wet method and high-temperature activation, and further maintains and regulates the pore distribution through freeze drying and solvent thermal treatment, so that the specific surface area of the activated carbon finally prepared reaches 1500-2000m 2 / g, and the pore volume retention rate is over 90%. This technology not only effectively solves the problems of insufficient carbon black purity, unstable pore structure and high energy consumption in the existing process, but also significantly improves the adsorption performance and chemical stability, making it widely used in water treatment, gas adsorption and catalyst carriers, etc., with the outstanding advantages of high efficiency, low consumption and environmental protection.
[0019] In addition, the method for preparing activated carbon by pyrolysis of waste tire carbon black according to the present invention may also have the following additional technical features:
[0020] Specifically, the electromagnetic assisted heating technology used in step 1 improves heating efficiency and reduces energy consumption through an alternating electromagnetic field, and the introduced trace oxidant (such as ozone or oxygen) is controlled at 1%-3% of the total atmosphere for local oxidation to promote the formation of initial functional groups on the carbon black surface, thereby improving the efficiency of subsequent activation reactions.
[0021] Specifically, the dynamic screening device in step 2 adopts a combined technology of airflow classification and cyclone separation, which can effectively distinguish carbon black particles with a particle size less than 10 microns and greater than 10 microns, and during the magnetic separation process, an alternating magnetic field is used to completely remove trace iron impurities (content less than 5%), thereby ensuring that the final carbon black purity reaches 95%-98%.
[0022] Specifically, in step 3, the low-temperature plasma treatment uses a mixed gas of nitrogen and hydrogen as a plasma reaction medium under low temperature conditions of 100-200°C, and enhances the stability of the carbon skeleton on the surface of carbon black through controllable radio frequency power (200-500W). The generated carbon black has a higher degree of graphitization and its structural stability is improved by 30%-50%.
[0023] Specifically, the surface functional group regulation in step 4 controls the gas ratio at 3:7 through the synergistic reaction of ozone and water vapor, and adjusts the reaction time within 2-4 hours; the density of the surface active groups (such as hydroxyl, carboxyl, and ester groups) of the obtained pyrolytic carbon black reaches 3-5 mmol / g, which effectively improves the adsorption performance of the activated carbon.
[0024] Specifically, in step 5, the wet activation is combined with the high-temperature activation process. The wet activation generates a preliminary pore structure by reacting in an autoclave at 180-250°C. The high-temperature activation introduces a mixed gas (such as carbon dioxide and water vapor) under vacuum conditions at 700-900°C, and controls the total gas flow rate at 200-400 mL / min, which significantly optimizes the micropore ratio and specific surface area of the activated carbon, and the final specific surface area reaches 1500-2000 m 2 / g.
[0025] Specifically, the freeze-drying method in step 6 adopts a gradual cooling method (from room temperature to -40°C or lower) to avoid the collapse of the pore structure, and ensures the integrity of the pore volume through long-term low-temperature drying (12-24 hours); the pore volume retention rate of the activated carbon obtained is between 90% and 95%.
[0026] Specifically, in step 7, the solvent thermal treatment is combined with ethanol, methanol or acetic acid solution at 120-160°C for 6-8 hours, and the pore distribution of the activated carbon is precisely regulated by controlling the solvent polarity and heating time. The final micropore ratio is 60%-70%, and the mesopore ratio is 20%-30%, which meets the needs of different industrial applications.
[0027] Specifically, the entire process can recycle more than 90% of the carbon black raw materials, and through the process steps of combining plasma treatment with high-temperature activation, the chemical stability and adsorption performance of activated carbon are significantly improved, so that its adsorption capacity in water purification applications is increased by 40%-50%.
[0028] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0030] Figure 1 A schematic diagram of the method for preparing activated carbon by pyrolyzing carbon black from waste tires according to the present invention;
[0031] Figure 2 It is a schematic diagram of experimental data of composite separation of waste tire pyrolysis carbon black according to the present invention;
[0032] Figure 3 It is a schematic diagram of experimental data of selective dynamic screening and magnetic impurity removal of the present invention;
[0033] Figure 4 This is a schematic diagram of experimental data of the carbon skeleton structure strengthening treatment of the present invention;
[0034] Figure 5 Schematic diagram of experimental data for regulating surface functional groups of the present invention;
[0035] Figure 6 Schematic diagram of experimental data of deep activation treatment of the present invention. DETAILED DESCRIPTION
[0036] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limitations of the present invention. On the contrary, embodiments of the present invention include all changes, modifications and equivalents that fall within the spirit and connotation of the appended claims.
[0037] The following describes a method for preparing activated carbon by pyrolyzing carbon black from waste tires according to an embodiment of the present invention in conjunction with the accompanying drawings.
[0038] like Figure 1-Figure 4 As shown, the method for preparing activated carbon by pyrolyzing carbon black from waste tires according to an embodiment of the present invention may include the following steps:
[0039] S1. Composite separation of waste tire pyrolysis carbon black:
[0040] a. In the first stage, low-temperature pyrolysis is carried out at 250-400℃ to decompose the volatile components in the tire and avoid damage to the carbon black structure;
[0041] b. In the second stage, medium-temperature pyrolysis is carried out at 400-600°C to generate gas phase products and primary carbon black, thereby enhancing the carbonization degree of carbon black;
[0042] c. In the third stage, high temperature pyrolysis is carried out at 600-750°C to strengthen the graphitization structure and chemical stability of carbon black;
[0043] Electromagnetic assisted heating technology is used in the graded pyrolysis process, and trace oxidants are introduced for controllable oxidation to optimize the initial activity of the carbon black surface.
[0044] It should be noted that, in the low-temperature pyrolysis stage described in this embodiment, the volatile components in the tire are decomposed by slowly heating and strictly controlling the temperature, thereby ensuring that the gas products are fully released and reducing the damage to the microstructure of the carbon black. In the medium-temperature pyrolysis stage, the carbonization degree of the primary carbon black is promoted by controlling the pyrolysis time and the temperature gradient, and the liquid and gas in the pyrolysis by-products are fully separated. In the high-temperature pyrolysis stage, electromagnetic assisted heating technology is combined to provide a uniform thermal field, and a trace amount of oxidant is introduced to realize a controllable surface oxidation reaction, thereby further improving the graphitization degree and chemical activity of the carbon black.
[0045] S2. Selective dynamic screening and removal of magnetic impurities. The pyrolysis products are dynamically screened through an airflow classification device to separate high-purity carbon black particles with a particle size of less than 10 microns. At the same time, magnetic separation technology is used to remove metal impurities and residual steel wire. The purity of carbon black reaches more than 95%.
[0046] It should be noted that in the airflow classification process described in this embodiment, the airflow velocity and cyclone separator parameters are adjusted to achieve accurate separation of particles of different particle sizes and improve the particle size uniformity of the carbon black product. The alternating magnetic field technology is used in the magnetic separation stage, combined with a multi-stage separation device, to efficiently remove trace metal impurities and residual steel wire to improve product purity. To ensure the high purity of the final carbon black, a secondary fine screening process can be added after screening and magnetic separation to effectively control the impurity content to further drop below 1%.
[0047] S3, carbon skeleton structure strengthening treatment, the screened pyrolytic carbon black is placed in a plasma reactor, and low-temperature plasma treatment (100-200°C) is carried out in a mixed atmosphere of nitrogen and a small amount of hydrogen to remove amorphous carbon and generate a stable carbon skeleton structure through hydrogenation:
[0048] It should be noted that in the plasma treatment process described in this embodiment, by optimizing the RF power and gas flow rate, it is ensured that the plasma acts evenly on the surface of the carbon black particles, thereby improving the overall efficiency of the treatment. The synergistic effect of the hydrogenation reaction in the mixed atmosphere of nitrogen and hydrogen not only enhances the chemical stability of the carbon skeleton, but also effectively reduces the surface defect density. After treatment, the small amount of volatile by-products generated in the reaction can be recovered in combination with the gas exhaust system, thereby further improving the environmental friendliness and resource utilization of the process.
[0049] S4. Surface functional group regulation: Plasma-treated pyrolytic carbon black is placed in a gas-solid mixed reaction device, and a mixed gas of ozone and water vapor is introduced to carry out surface functional group regulation reaction at 80-150°C to generate a large number of hydroxyl, carboxyl and ester functional groups, thereby improving the surface activity of carbon black.
[0050] It should be noted that in the process of surface functional group regulation described in this embodiment, the flow ratio of ozone and water vapor and the reaction time are precisely controlled to ensure that the functional groups are evenly distributed on the carbon black surface. An efficient gas circulation system is provided in the reaction device to avoid uneven local reactions and improve the consistency of surface modification. After treatment, the generated hydroxyl, carboxyl and ester groups are stabilized in combination with a rapid cooling process, effectively preventing secondary decomposition of the functional groups caused by high-temperature reactions.
[0051] S5, deep activation treatment, the surface modified carbon black is mixed with potassium hydroxide solution in a mass ratio of 1:2-3, and a wet activation reaction is carried out in an autoclave at 180-250°C for 2-4 hours; then, the activated carbon black is heated to 700-900°C under vacuum conditions for high-temperature activation, and a mixed gas is introduced at the same time to further optimize the pore structure and increase the specific surface area.
[0052] It should be noted that, in the wet activation stage described in this embodiment, by optimizing the concentration of potassium hydroxide solution and the stirring speed, it is ensured that the activator fully penetrates into the micropores inside the carbon black and improves the activation efficiency. In the high-temperature activation process, the collapse of the carbon black structure is avoided by segmented heating and precise temperature control. At the same time, the proportion and flow rate of the introduced gas are optimized to regulate the distribution of micropores and mesopores. Finally, after activation, a gas exhaust purification system is used to recover high-temperature by-products, thereby realizing a green process and improving resource utilization.
[0053] S6. Post-treatment of activated carbon: The activated carbon product is quickly cooled to room temperature, repeatedly washed with deionized water until neutral, and dried by freeze drying (-40°C to -60°C) to retain the integrity of the pore structure, and finally a high-performance activated carbon product is obtained.
[0054] It should be noted that the rapid cooling technology used in the cooling process described in this embodiment can avoid shrinkage or collapse of the pore structure due to excessive temperature difference, thereby ensuring the stability of the product structure. In the washing stage, the deionized water flushing system is continuously circulated to improve the cleaning efficiency and reduce the impact of activator residues on product performance. In the freeze-drying process, the gradual cooling and vacuum environment are combined to further improve the drying uniformity, while reducing the damage to the pore structure and ensuring the high adsorption performance of the activated carbon.
[0055] S7. Performance optimization and functional orientation. The prepared activated carbon is subjected to pore regulation and structural orientation treatment. Through solvent thermal treatment (using ethanol or acetic acid solution to react at 120-160°C for 6-8 hours), the proportion of micropores, mesopores and macropores on the surface of the activated carbon is regulated to meet the pore size requirements of different application scenarios.
[0056] It should be noted that in the solvent thermal treatment process described in this embodiment, the solvent concentration and reaction temperature are adjusted to further refine the precise control of the ratio of micropores and mesopores to meet different application requirements. A dynamic stirring system is introduced into the treatment device to ensure sufficient contact between the solvent and the activated carbon particles, thereby improving the consistency and efficiency of pore control. After treatment, low-temperature drying and a vacuum environment are combined to stabilize the pore structure to avoid macropore collapse or micropore clogging, thereby significantly improving the adsorption performance and long-term stability of the activated carbon.
[0057] The following is a detailed data description combined with the experimental steps:
[0058] S1: Composite separation of waste tire pyrolysis carbon black
[0059] Experimental steps:
[0060] 1. 2kg of waste tires are added into the multi-chamber pyrolysis device, and nitrogen is introduced into the reaction chamber for protection.
[0061] 2. In the first stage, the mixture was heated to 300°C at a heating rate of 5°C / min and maintained for 1 hour to release the volatile components.
[0062] 3. In the second stage, the temperature is raised to 550°C and maintained for 2 hours to generate primary carbon black, and the pyrolysis gas and liquid by-products are separated.
[0063] 4. In the third stage, the temperature is raised to 700°C, 0.5% ozone (volume ratio) is added as an oxidant, and maintained for 1 hour to complete the graphitization of carbon black.
[0064] Graded pyrolysis can effectively improve the purity and graphitization degree of carbon black. Especially after adding a trace amount of ozone to control the oxidation reaction, the chemical stability of the carbon black surface is significantly enhanced, which is convenient for subsequent processing.
[0065] S2: Selective dynamic screening and magnetic impurity removal
[0066] Experimental steps:
[0067] 1. After the pyrolysis is completed, the product is cooled to room temperature and screened using an airflow classifier. The airflow velocity is adjusted to 20 m / s to separate particles with a particle size of less than 10 microns.
[0068] 2. After screening, it is processed through a multi-stage magnetic separation system, using an alternating magnetic field strength of 2000 Gauss to remove metal impurities.
[0069] 3. Test the particle size distribution and impurity content of the final product.
[0070] The combination of airflow classification and multi-stage magnetic separation effectively improves the purity and particle size uniformity of carbon black, ensuring the consistency of the subsequent plasma treatment effect.
[0071] S3: Carbon skeleton structure strengthening treatment.
[0072] Experimental steps:
[0073] 1. The screened carbon black (particle size less than 10 microns) is placed in a plasma reactor and a mixture of nitrogen and hydrogen (flow ratio 85:15) is introduced.
[0074] 2. The RF power is controlled at 400W, the temperature is adjusted to 200°C, and the reaction time is 30 minutes.
[0075] 3. Test the amorphous carbon residue rate, graphitization degree and pore structure of the treated carbon black.
[0076] The optimized plasma treatment process significantly reduces the amorphous carbon content (to 6%) under low temperature conditions, significantly improves the degree of graphitization, and provides a stable carbon skeleton for subsequent pore and functional group regulation.
[0077] S4: Surface functional group regulation
[0078] Experimental steps:
[0079] 1. The plasma-treated carbon black was placed in a gas-solid mixed reaction device, and ozone (concentration 1.5%) and water vapor (flow rate 150 mL / min) were introduced.
[0080] 2. The temperature is controlled at 120°C and the reaction time is 4 hours.
[0081] 3. Detect the functional group density of the modified carbon black.
[0082] Under the conditions of ozone concentration of 1.5% and water vapor flow rate of 150 mL / min, the functional group density reached its maximum value, providing high surface activity for the activated carbon and significantly enhancing the adsorption performance.
[0083] 5: Deep activation treatment
[0084] Experimental steps:
[0085] 1. Mix the modified carbon black with potassium hydroxide solution (mass ratio of 1:2.5) and place it in an autoclave at 180°C for 3 hours.
[0086] 2. After treatment, heat to 800°C in a vacuum furnace, introduce a mixed gas of CO and HO (flow rate 300 mL / min), and maintain for 2 hours.
[0087] 3. Test the pore structure and specific surface area of activated carbon.
[0088] The two-step process of wet activation combined with high temperature activation is adopted, and the specific surface area of carbon black is significantly increased to 1800m 2 / g, the pore structure is uniform and the proportion of micropores accounts for more than 80%.
[0089] Through the above experimental steps and data verification, this technical solution has demonstrated significant innovation and optimization effects in each process link. The properties of the activated carbon finally prepared are as follows:
[0090] Specific surface area: 1800m 2 / g;
[0091] Pore volume: Total pore volume 0.80cm 3 / g, micropore volume accounts for 80%;
[0092] Adsorption performance: The adsorption efficiency of heavy metals in water is increased by 40%-50%.
[0093] Specifically, the pyrolysis process is divided into three stages: low temperature, medium temperature and high temperature. The volatile components are decomposed in the low temperature stage to avoid damage to the carbon black structure. The medium temperature stage promotes carbonization of carbon black and removes more impurities. The high temperature stage uses electromagnetic assisted heating technology and the introduction of trace oxidants to generate initial active sites on the surface of carbon black and increase the degree of graphitization, thereby improving the chemical stability and activation potential of carbon black from the source. Subsequently, airflow screening combined with multi-stage magnetic separation technology is used to further remove metal impurities and non-carbon components, significantly improving the purity of carbon black (up to more than 96%). At the same time, the particle size of carbon black is controlled below 10 microns, laying the foundation for subsequent processing. In the carbon skeleton strengthening treatment link, low-temperature plasma technology is introduced to nitrogen The mixed atmosphere of ozone and hydrogen acts synergistically to remove amorphous carbon and form a stable carbon skeleton structure, which significantly improves the degree of graphitization (up to 65%) and ensures that the pore structure of activated carbon is not destroyed during the high-temperature activation stage. In the process of surface functional group regulation, the mixed gas of ozone and water vapor is used to generate functional groups such as hydroxyl, carboxyl and ester groups at a lower temperature, which improves the surface activity of carbon black and makes it have a higher adsorption capacity. In the deep activation stage, the wet activation is completed in an autoclave through a process combining wet activation with high-temperature activation to ensure that the activator fully penetrates and generates a preliminary pore structure. Subsequently, the mixed gas is introduced during the high-temperature activation to further optimize the pore distribution, which significantly improves the specific surface area (up to 1800m 2 / g) and micropore proportion (micropore volume accounts for 80%). Finally, in the post-processing stage, the freeze-drying technology is used to retain the integrity of the pore structure of the activated carbon, while further improving the specific surface area and adsorption performance. The overall technical solution solves the problems of carbon black impurities, uncontrollable porosity, and high energy consumption in the existing technology through phased refined control and multi-process coordination, and ultimately achieves the efficient preparation of high-performance activated carbon, providing technical support for its application in water treatment, gas adsorption, and catalyst carriers.
[0094] In one embodiment of the present invention, Figure 1 As shown, the electromagnetic assisted heating technology used in step 1 improves heating efficiency and reduces energy consumption through an alternating electromagnetic field, and the introduced trace oxidant (such as ozone or oxygen) is controlled at 1%-3% of the total atmosphere for local oxidation to promote the formation of initial functional groups on the carbon black surface, thereby improving the efficiency of subsequent activation reactions.
[0095] It should be noted that in the electromagnetic-assisted heating process described in this embodiment, the frequency (range 1-10kHz) and intensity of the alternating electromagnetic field are precisely controlled to ensure heating uniformity and reduce local overheating, thereby improving the stability and efficiency of the pyrolysis process. When a trace oxidant is introduced, the gas flow control and distribution adjustment technology are combined to achieve the spatial selectivity of the oxidation reaction, further optimizing the generation distribution of functional groups on the surface of carbon black. At the same time, a real-time monitoring system is used to feedback control the oxidant concentration and reaction products to avoid damage to the carbon black structure caused by excessive oxidation, thereby maximizing the number and uniformity of surface active sites.
[0096] In one embodiment of the present invention, Figure 1 As shown, the dynamic screening device in step 2 adopts the combined technology of airflow classification and cyclone separation, which can effectively distinguish carbon black particles with a particle size less than 10 microns and greater than 10 microns, and the alternating magnetic field is used during the magnetic separation process to achieve thorough removal of trace iron impurities (content less than 5%), thereby ensuring that the final carbon black purity reaches 95%-98%.
[0097] It should be noted that in the dynamic screening process described in this embodiment, by optimizing the air flow velocity (range 15-25m / s) and the grading angle, the precise separation of particles of different sizes is achieved to ensure the uniformity of the target carbon black particles. After cyclone separation, a multi-stage separation device is used to recover and screen the remaining large particles for the second time to reduce screening losses and improve separation efficiency. In the magnetic separation stage, the alternating magnetic field frequency (range 50-200Hz) and magnetic field strength (2000-5000 Gauss) are adjusted to completely remove trace metal impurities, ensuring that the purity of carbon black is stable at more than 95%, while effectively reducing the impact of non-carbon components on subsequent processes.
[0098] In one embodiment of the present invention, Figure 1 As shown, in step 3, the low-temperature plasma treatment uses a mixed gas of nitrogen and hydrogen as a plasma reaction medium under low temperature conditions of 100-200°C, and enhances the stability of the carbon skeleton on the surface of carbon black through controllable radio frequency power (200-500W). The generated carbon black has a higher degree of graphitization and its structural stability is improved by 30%-50%.
[0099] It should be noted that in the low-temperature plasma treatment process described in this embodiment, the range of change of the RF power is precisely controlled (such as dynamic power adjustment of 200-500W) to ensure that the plasma energy density is adapted to the surface characteristics of the carbon black particles, and excessive energy damage to the microporous structure is avoided. The mixing ratio of nitrogen and hydrogen (such as 90:10 to 80:20) is further optimized, and the chemical stability of the carbon skeleton is enhanced and surface defects are repaired through hydrogenation reaction, thereby improving the degree of graphitization. In order to ensure the uniformity of the treatment effect, a multi-channel rotating plasma reaction chamber design is adopted to enable the carbon black particles to receive energy evenly during the reaction, and finally obtain a carbon black with a more stable structure and higher surface activity.
[0100] In one embodiment of the present invention, Figure 1 As shown, the surface functional group regulation in step 4 controls the gas ratio at 3:7 through the synergistic reaction of ozone and water vapor, and adjusts the reaction time within 2-4 hours; the density of the surface active groups (such as hydroxyl, carboxyl, and ester groups) of the obtained pyrolytic carbon black reaches 3-5 mmol / g, which effectively improves the adsorption performance of the activated carbon. The wet activation and high-temperature activation are combined in step 5. The wet activation generates a preliminary pore structure by reacting in an autoclave at 180-250°C. The high-temperature activation is performed by introducing a mixed gas (such as carbon dioxide and water vapor) under vacuum conditions at 700-900°C, and the total gas flow rate is controlled at 200-400 mL / min, which significantly optimizes the micropore ratio and specific surface area of the activated carbon, and the final specific surface area reaches 1500-2000m 2 / g, the freeze-drying method in step 6 adopts a gradual cooling method (from room temperature to -40°C or lower) to avoid the collapse of the pore structure, and the integrity of the pore volume is ensured by long-term low-temperature drying (12-24 hours); the pore volume retention rate of the obtained activated carbon is between 90% and 95%, and the solvent thermal treatment in step 7 is combined with ethanol, methanol or acetic acid solution at 120-160°C for 6-8 hours, and the pore distribution of the activated carbon is precisely regulated by controlling the solvent polarity and heating time. The final micropore ratio is 60%-70%, and the mesopore ratio is 20%-30%, which meets the needs of different industrial applications. The entire process can recover more than 90% of the carbon black raw materials, and the process steps combined with plasma treatment and high-temperature activation significantly improve the chemical stability and adsorption performance of the activated carbon, so that its adsorption capacity in water purification applications is increased by 40%-50%.
[0101] It should be noted that in the surface functional group regulation stage described in this embodiment, by introducing the segmented gas flow control technology, the mixed gas of ozone and water vapor is introduced in proportion and segmented to ensure the uniformity of the reaction and the high-density distribution of the functional groups. In the wet activation process, the contact efficiency between the activator and the carbon black particles is improved by the dynamic stirring system in the autoclave, so that the formation of the initial pore structure is more uniform, while reducing the occurrence of invalid reactions. In high-temperature activation, a step-by-step heating strategy (heating rate 3-5°C / min) and dynamic airflow control technology are used to optimize the pore size distribution and avoid pore collapse, thereby maximizing the micropore ratio and specific surface area. In the freeze-drying and solvent thermal treatment stages, precise temperature control and high-efficiency solvent recovery devices are used, which not only retains the integrity of the pore structure to the greatest extent, but also realizes the greening of the process and a significant improvement in resource utilization.
[0102] Specifically, electromagnetic assisted heating technology is introduced during the pyrolysis process, combined with trace oxidants, and the initial functional group generation on the carbon black surface is optimized by precisely controlling the atmosphere and pyrolysis conditions, laying the foundation for subsequent reactions. Secondly, airflow classification and multi-stage magnetic separation technology are used to efficiently remove metal impurities and non-carbon components, significantly improving the purity of carbon black, and ensuring the consistency of subsequent treatment by precisely controlling the particle size. Subsequently, low-temperature plasma technology is combined to strengthen the carbon skeleton, and the stability and degree of graphitization of carbon black are greatly improved through hydrogenation and surface defect repair. In the regulation of surface functional groups, ozone and water vapor work synergistically to generate high-density active groups such as hydroxyl and carboxyl, further improving the surface activity of carbon black. In the activation stage, wet activation is used. The combination of chemistry and high-temperature activation not only optimizes the pore structure, but also significantly improves the specific surface area and micropore ratio to achieve ideal adsorption performance. In the post-processing stage, the freeze-drying technology is used to maintain the integrity of the pore structure to avoid the pore collapse problem in the traditional drying process. At the same time, the solvent thermal treatment technology is used to accurately control the pore size distribution to meet the needs of different industrial applications. In the entire process, by optimizing resource utilization and energy consumption control, the carbon black resource utilization rate is over 90%, and the energy consumption is reduced by 30%-40%. It effectively solves the problems of insufficient carbon black purity, unstable pore structure, high energy consumption, etc. in the existing process, and significantly improves the adsorption performance and chemical stability of activated carbon. The activated carbon finally prepared has 1500-2000m 2 / g specific surface area, 90%-95% pore volume retention rate, and 40%-50% adsorption performance improvement, while having the characteristics of low energy consumption and high environmental protection, it is widely used in water treatment, gas adsorption and catalyst carrier and other fields.
[0103] In summary, the method for preparing activated carbon by pyrolyzing carbon black from waste tires in the embodiment of the present invention optimizes the generation of functional groups on the surface of carbon black by using electromagnetic assisted heating combined with a pyrolysis technology of a trace oxidant, and improves the purity and particle size uniformity of carbon black by airflow classification and magnetic separation technology. Low-temperature plasma treatment enhances the stability and graphitization degree of the carbon skeleton, and the synergistic effect of ozone and water vapor regulates the density of surface functional groups, laying a foundation for improving the adsorption performance. The pore structure is optimized by combining wet method with high-temperature activation, and freeze drying and solvent thermal treatment further maintain and regulate the pore distribution. The specific surface area of the activated carbon finally prepared reaches 1500-2000m 2 / g, and the pore volume retention rate is over 90%. This technology not only effectively solves the problems of insufficient carbon black purity, unstable pore structure and high energy consumption in the existing process, but also significantly improves the adsorption performance and chemical stability, making it widely used in water treatment, gas adsorption and catalyst carriers, etc., with the outstanding advantages of high efficiency, low consumption and environmental protection.
[0104] In the description of this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0105] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0106] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention.
Claims
1. A method for preparing activated carbon by pyrolyzing carbon black from waste tires, characterized in that: The following steps are involved: S1. Composite separation of waste tire pyrolysis carbon black: a. In the first stage, low-temperature pyrolysis is carried out at 250-400°C to decompose the volatile components in the tire and avoid damage to the carbon black structure; b. In the second stage, medium-temperature pyrolysis is carried out at 400-600°C to generate gas phase products and primary carbon black, thereby enhancing the carbonization degree of carbon black; c. In the third stage, high temperature pyrolysis is carried out at 600-750°C to strengthen the graphitization structure and chemical stability of carbon black; Electromagnetic assisted heating technology is used in the graded pyrolysis process, and trace oxidants are introduced for controlled oxidation to optimize the initial activity of the carbon black surface; S2, Selective dynamic screening and magnetic impurity removal, the pyrolysis products are dynamically screened through an airflow classification device to separate high-purity carbon black particles with a particle size of less than 10 microns, and magnetic separation technology is used to remove metal impurities and residual steel wire, and the purity of carbon black reaches more than 95%; S3, carbon skeleton structure strengthening treatment, the screened pyrolytic carbon black is placed in a plasma reactor, and low-temperature plasma treatment (100-200°C) is performed in a mixed atmosphere of nitrogen and a small amount of hydrogen to remove amorphous carbon and generate a stable carbon skeleton structure through hydrogenation; S4, surface functional group regulation, placing the plasma-treated pyrolytic carbon black in a gas-solid mixed reaction device, introducing a mixed gas of ozone and water vapor, and performing a surface functional group regulation reaction at 80-150°C to generate a large number of hydroxyl, carboxyl and ester functional groups, thereby improving the surface activity of the carbon black; S5, deep activation treatment, mixing the surface-modified carbon black with potassium hydroxide solution in a mass ratio of 1:2-3, and performing wet activation reaction in an autoclave at 180-250°C for 2-4 hours; then, heating the activated carbon black to 700-900°C under vacuum conditions for high-temperature activation, while introducing a mixed gas to further optimize the pore structure and increase the specific surface area; S6, post-treatment of activated carbon, the activated carbon product is quickly cooled to room temperature, repeatedly washed with deionized water until neutral, and dried by freeze drying (-40°C to -60°C) to retain the integrity of the pore structure, and finally a high-performance activated carbon product is obtained; S7. Performance optimization and functional orientation. The prepared activated carbon is subjected to pore regulation and structural orientation treatment. Through solvent thermal treatment (using ethanol or acetic acid solution to react at 120-160°C for 6-8 hours), the proportion of micropores, mesopores and macropores on the surface of the activated carbon is regulated to meet the pore size requirements of different application scenarios.
2. The method for preparing activated carbon by utilizing waste tire pyrolysis carbon black according to claim 1, characterized in that: The electromagnetic assisted heating technology used in step 1 improves heating efficiency and reduces energy consumption through an alternating electromagnetic field, and the introduced trace oxidant (such as ozone or oxygen) is controlled at 1%-3% of the total atmosphere for local oxidation to promote the formation of initial functional groups on the carbon black surface, thereby improving the efficiency of subsequent activation reactions.
3. The method for preparing activated carbon by utilizing waste tire pyrolysis carbon black according to claim 1, characterized in that: The dynamic screening device in step 2 adopts the combined technology of airflow classification and cyclone separation, which can effectively distinguish carbon black particles with a particle size less than 10 microns and greater than 10 microns. In the magnetic separation process, the alternating magnetic field is used to completely remove trace iron impurities (content less than 5%), thereby ensuring that the final carbon black purity reaches 95%-98%.
4. The method for preparing activated carbon by utilizing waste tire pyrolysis carbon black according to claim 1, characterized in that: In step 3, low-temperature plasma treatment is carried out at a low temperature of 100-200°C, using a mixed gas of nitrogen and hydrogen as a plasma reaction medium, and enhancing the stability of the carbon skeleton on the surface of carbon black through controllable radio frequency power (200-500W). The generated carbon black has a higher degree of graphitization and its structural stability is improved by 30%-50%.
5. The method for preparing activated carbon by utilizing waste tire pyrolysis carbon black according to claim 1, characterized in that: The surface functional group regulation in step 4 controls the gas ratio at 3:7 through the synergistic reaction of ozone and water vapor, and adjusts the reaction time within 2-4 hours; the density of the surface active groups (such as hydroxyl, carboxyl, and ester groups) of the obtained pyrolytic carbon black reaches 3-5 mmol / g, which effectively improves the adsorption performance of the activated carbon.
6. The method for preparing activated carbon by utilizing waste tire pyrolysis carbon black according to claim 1, characterized in that: In step 5, the wet activation is combined with the high-temperature activation process. The wet activation generates a preliminary pore structure through an autoclave reaction at 180-250°C. The high-temperature activation introduces a mixed gas (such as carbon dioxide and water vapor) under vacuum conditions at 700-900°C, and controls the total gas flow rate at 200-400mL / min, which significantly optimizes the micropore ratio and specific surface area of the activated carbon. The final specific surface area reaches 1500-2000m 2 / g.
7. The method for preparing activated carbon by utilizing waste tire pyrolysis carbon black according to claim 1, characterized in that: In step 6, the freeze-drying method adopts a gradual cooling method (from room temperature to -40°C or lower) to avoid the collapse of the pore structure, and ensures the integrity of the pore volume through long-term low-temperature drying (12-24 hours); the pore volume retention rate of the activated carbon obtained is between 90% and 95%.
8. The method for preparing activated carbon by utilizing waste tire pyrolysis carbon black according to claim 1, characterized in that: In step 7, the solvent thermal treatment is combined with ethanol, methanol or acetic acid solution at 120-160°C for 6-8 hours. The pore distribution of the activated carbon is precisely controlled by controlling the solvent polarity and heating time. The final micropore ratio is 60%-70%, and the mesopore ratio is 20%-30%, which meets the needs of different industrial applications.
9. The method for preparing activated carbon by utilizing waste tire pyrolysis carbon black according to claim 1, characterized in that: The entire process can recycle more than 90% of the carbon black raw materials, and through the process steps of combining plasma treatment with high-temperature activation, the chemical stability and adsorption performance of activated carbon are significantly improved, increasing its adsorption capacity in water purification applications by 40%-50%.
Citation Information
Cited By
Rubber composition for lithium battery with low metal ion precipitation, preparation method of rubber composition and valve
CN121005997A
A rubber composition for a lithium battery with low metal ion precipitation, a method of manufacturing the same, and a valve
CN121005997B
A silicon-carbon composite electrode material and its preparation method
CN122667557A